Instrumentos mediadores em reuniões pedagógicas - Almeida, Maria Angélica Durães Mendes de (2004)
This dissertation aims at investigating how instruments present at planning texts and pedagogical meetings can mediate the actions that occur during this school work activity. The focus of this paper was the work of the school coordinator in organizing the meetings and mediate the interactions from three specific instruments: the role distribution, the theoretical texts and the questions. Through the research we intend to contribute to the understanding of the educational work situation, to the study of the school coordinator action on teachers continuous formation and to the awareness of instrumental mediated knowledge construction on work activity. The research is based on the following theoretical references: (1) the Socio-diseursive Interactionism (Bronekart, 1997) as theoretical frame to the understanding of human action and to the analysis of verbal productions; (2) the diseussion between prescribed work and work dane (Clot 1999, 2001) to the understanding of actions at work activities and (3) the debate on verbal interactions on dialogie activity (Kerbrat-Orecchioni, 1991, 1992, 1998). A group of 14 professionals of a private sehool in Sao Paulo took part on the study in work activity at pedagogieal meetings, among them the researcher as the coordinator in eharge. Three meetings and their respeetive planning texts were studied through the analysis of the language aetion situation (Bronekart, 1997), types of question (Kerbrat- Orecchioni, 1991), the perfonned actions (Groupe LAF, 2002) and the speeeh tums (Kerbrat-Orecchioni, 1992,1998)